The Effectiveness of Explanation Methods of Lectures and Poster Media on Stunting Knowledge in Eligible Woman in Aceh Jaya Regency - Sari, Fani Septria; Duana, Maiza (Universitas Teuku Umar, 2022)
Nutritional status is a condition caused by a balance between nutrient intake from food needed for body metabolism. The aim was to determine the effectiveness of knowledge about stunting before or after counseling the lecture method and poster media for women of childbearing age in Alue Ambang Village, Teunom District, Aceh Jaya Regency. The type of this research is Quasi-experimental design with pre-test and post-test designs. The population of this study amounted to 250 people. The sample in this are 154 people. The data were tested with the Wilcoxon test. The research conducted, it is known that counseling using the lecture method and poster media regarding knowledge of stunting in women of childbearing age is considered very effective, it can be seen from the level of knowledge of women of childbearing age about stunting after being given counseling their knowledge increases compared to before being given counseling. P Value 0.000<0.05, which means statistically it shows there is a difference in increasing knowledge of lecture method counseling and poster media about stunting knowledge in women of childbearing age. It is recommended that health workers and Integrated Health Center cadres use the lecture method and poster media in conducting counseling.